Difficulties and facilities perceived by nursing workers in relation to exposure to biological material - Bispo, Gisele do Carmo; Araujo, Mariana de Oliveira; Portela, Pollyana Pereira; Oliveira, Silvânia Sales de; Santana, Thiago da Silva (Revista de Enfermagem da UFPI, 2023)
Objective: To describe the difficulties and/or facilities perceived by nursing workers in situations involving exposure to biological material. Methods: This was a qualitative study carried out with eight female mid- and higher-level nursing workers who had been working for at least six months in the Medical and Surgical Clinics of a public general hospital. Data was collected through semi-structured interviews, carried out remotely (videoconferencing) and in person, between December 2021 and April 2022. The Content Analysis technique was used to analyze the data. Results: The difficulties were: high demand; non-adherence to Personal Protective Equipment; inadequate disposal of materials used by students; management of emotional issues; implementation of the protocol; lack of knowledge of the source patient; and non-recognition of exposure by the exposed worker. As for facilities, these were: aspects related to care (guidance, reception, service and agility); control of the situation; segregation of hospital waste; knowledge of the protocol and of the source patient. Conclusion: There is a need for interventions that seek to overcome the difficulties and strengthen the facilities found in this study to reduce/avoid the occurrence of possible exposures and promote the quality of the service provided.